Antenatal care in The Gambia: Missed opportunity for information, education and communication - Jaiteh Lamin ES; Hydara Abba; Anya Samuel E (BMC, 2008)
Abstract Background Antenatal care is widely established and provides an opportunity to inform and educate pregnant women about pregnancy, childbirth and care of the newborn. It is expected that this would assist the women in making choices that would contribute to good pregnancy outcome. We examined the provision of information and education in antenatal clinics from the perspective of pregnant women attending these clinics. Methods A cross sectional survey of 457 pregnant women attending six urban and six rural antenatal clinics in the largest health division in The Gambia was undertaken. The women were interviewed using modified antenatal client exit interview and antenatal record review questionnaires from the WHO Safe Motherhood Needs Assessment kit. Differences between women attending urban and rural clinics were assessed using the Chi-square test. Relative risks with 95% confidence intervals are presented. Results Ninety percent of those interviewed had attended the antenatal clinic more than once and 52% four or more times. Most pregnant women (70.5%) said they spent 3 minutes or less with the antenatal care provider. About 35% recalled they were informed or educated on diet and nutrition, 30.4% on care of the baby, 23.6% on family planning, 22.8% on place of birth and 19.3% on what to do if there was a complication. About 25% of pregnant women said they were given information about the progress of their pregnancy after consultation and only 12.8% asked their provider any question. Awareness of danger signs was low. The proportions of women that recognised signs of danger were 28.9% for anaemia, 24.6% for hypertension, 14.8% for haemorrhage, 12.9% for fever and 5% for puerperal sepsis. Prolonged labour was not recognised as a danger sign. Women attending rural antenatal clinics were 1.6 times more likely to recognise signs of anaemia and hypertension as indicative of danger compared to women attending urban antenatal clinics. Conclusion Information, education and communication during antenatal care in the largest health division are poor. Pregnant women are ill-equipped to make appropriate choices especially when they are in danger. This contributes to the persistence of high maternal mortality ratios in the country.